The Type 3 Deiodinase Is a Critical Modulator of Thyroid Hormone Sensitivity in the Fetal Brain - Martinez, Maria Elena; Hernandez, Arturo (Frontiers in Neuroscience, 2021)
Thyroid hormones (TH) are critical for the development and function of the central nervous system (CNS). Although their effects on the rodent brain peak within 2–3 weeks postnatally, the fetal brain has been found largely insensitive to exogenously administrated TH. To address this issue, here we examined gene expression in brains from mouse fetuses deficient in the type 3 deiodinase (DIO3), the selenoenzyme responsible for clearing TH. At embryonic day E18.5 qPCR determinations indicated a marked increase in the mRNA expression of T3-responsive genes Klf9 and Nrgn. The increased expression of these genes was confirmed by in situ hydridization in multiple areas of the cortex and in the striatum. RNA sequencing revealed 246 genes differentially expressed (70% up-regulated) in the brain of E18.5 Dio3−/− male fetuses. Differential expression of 13 of these genes was confirmed in an extended set of samples that included females. Pathway analyses of differentially expressed genes indicated enrichment in glycolysis and signaling related to axonal guidance, synaptogenesis and hypoxia inducible factor alpha. Additional RNA sequencing identified 588 genes differentially expressed (35% up-regulated) in the brain of E13.5 Dio3−/− male fetuses. Differential expression of 13 of these genes, including Klf9, Hr, and Mgp, was confirmed in an extended set of samples including females. Although pathway analyses of differentially expressed genes at E13.5 also revealed significant enrichment in axonal guidance and synaptogenesis signaling, top enrichment was found for functions related to the cell cycle, aryl hydrocarbon receptor signaling, PCP and kinetochore metaphase signaling pathways and mitotic roles of polo-like kinase. Differential expression at E13.5 was confirmed by qPCR for additional genes related to collagen and extracellular matrix and for selected transcription factors. Overall, our results demonstrate that the rodent fetal brain is sensitive to TH as early as E13.5 of gestational age, and suggest that TH distinctly affects brain developmental programs in early and late gestation. We conclude that DIO3 function is critical to ensure an adequate timing for TH action in the developing brain and is probably the main factor underlying the lack of effects on the fetal brain observed in previous studies after TH administration.